LEGAL DETERMINATION VS JUSTICE AS ELEMENTS OF THE PRINCIPLE OF THE RULE OF LAW - SKOREIKO, VASYL (Ehrlich's Journal, 2023)
The article examines legal and justice as elements of the rule of law principle. The principle of the rule of law is defined as an indicator of the democratic development of society and an integral component of the rule of law. It is emphasized that the recognition of the principle of the rule of law establishes the requirement for lawmaking acts and law-enforcement practice not only to comply with the signs of normativity and to correspond to the letter of the law, but also, importantly, to ensure compliance of the current legislation with the spirit of the law and the idea of the highest value of human rights. It is emphasized that the principle of the rule of law does not involve declarative recognition of human rights and freedoms, but first of all, the procedure for their observance, provision, implementation and protection. Inalienability, inviolability of human rights, their reliable protection is a defining criterion of the rule of law. At the same time, protection against any illegal and arbitrary intervention of state authorities in human rights and freedoms must be carried out by an independent and impartial court. It is noted that the indicators of the rule of law are to court, providing legal protection and challenging the actions of public authorities before an independent impartial court, equality before the law, legal certainty, and the execution of a court decision in the event that it becomes final. It was established that in the activity of judicial bodies, the direct application of the principle of the rule of law and its effectiveness should be recognized as the fundamental basis of the modern legal order. However, in order for this provision to be transferred from the category of goals and embodied in a concrete legal result, special legal tools for the transformation of this goal are necessary. It was concluded that ensuring the effectiveness of the principle of the rule of law is not possible without recognition and implementation in legal life of the principles of legal certainty and justice. The interaction of the integral elements of rule of law – legal certainty and justice reflects aspects: formal – the presence of an effective mechanism for the protection of human rights and freedoms though justice and substantive – the presence of fair requirements in legal prescriptions.